An evaluation of potential dustbathing substrates for commercial broiler chickens. (22nd December 2017) - Baxter, M.; Bailie, C. L.; O'Connell, N. E.
Abstract : Provision of an appropriate dustbathing substrate may allow broiler chickens to satisfy a natural motivation and give them an opportunity to exercise. The main aim of this study was to evaluate the extent to which different substrates promote dustbathing behaviour in broilers. The trial was replicated over three production cycles in one commercial broiler house, with 22 000 Ross broilers housed per cycle. The birds were provided with access to five experimental substrates from day 10 of the 6-week production cycle. The substrates included the following: (1) peat (P), (2) oat hulls (OH), (3) straw pellets (SP), (4) clean wood shavings (WS), and (5) litter control (C). The substrates were provided in 15 steel rings (1.1 m in diameter, three rings per substrate) dispersed throughout the house. The level of occupancy of the rings, behaviours performed in each substrate, and the effect of ring position (central or edge of house) were assessed in weeks 3, 4, 5 and 6 using scan sampling from video footage. Where substrates successfully promoted dustbathing, the length and components of the bouts (including number of vertical wing shakes and ground pecks) were also assessed. Results showed that birds used P significantly more than the remaining substrates for dustbathing ( P <0.001). Oat hulls were the second most preferred substrate for dustbathing, with significantly more birds dustbathing in the OH compared with SP, WS and C ( P <0.001). The least sitting inactive was also seen in the P and OH rings compared with the SP, WS and C ( P <0.001). The highest levels of foraging were recorded in the P, OH and WS compared with SP and the C. Position of the rings did not affect the types of behaviours performed in any substrate, although overall more birds were counted in the central compared with edge rings ( P= 0.001). More detailed information on dustbathing behaviour was only recorded in the P and OH treatments, and there were no differences in the length of dustbathing bout, or components of the bout between them ( P> 0.05). The use of OH is likely to be more environmentally sustainable than that of P, and our results suggest that this substrate is relatively successful in promoting dustbathing. However, a preference was still observed for P and further work should investigate whether other suitable substrates could better reflect its qualities.